A Review on Historical Development of Sukuk - Abdulsoma, Thoarlim; Mohamad Zaharuddin, Zakaria; Ahmad Zaki, Salleh; Mushaddad, Hasbullah (2016)
This paper reviews the historical development of sukuk with reference to issues aroused in the development process. Some opinions argues that the current practices of sukuk are contrary to the Shariah law. While another views that it complies with the law. Thus, the understanding of the concepts is crucial to ensure the legality of the instrument based on Shariah Law. This study employs textual analysis to identify the main characteristics of sukuk as practiced in Malaysia. Some selected term sheets of sukuk are analyzed. In addition, a semi-structured interview is conducted on samples of Malaysian scholars and practitioners in order to get their practical views on these issues. This study found that sukuk is a type of securitization that based on underlying asset compared to conventional bond that mainly based on loan with interest. The return of sukuk comes from the underlying assets and not from the interest as offered by the conventional bond. Finally, Sukuk has been recognized as Shariah compliant instrument in the Islamic Capital Market worldwide as the best option for the investors who are looking forward to invest in the Islamic Capital Market. It accommodates the investor's needs to invest in Islamic capital market either for Muslims or non-Muslims worldwide.